Pelatihan Pemrograman Menggunakan AppIventor di Sekolah Dasar sebagai bagian Literasi Digital di Era Industri 4.0 - Rizal, Adhi; Primajaya, Aji; Haodudi Nurkifli, E.; Ibnu Adam, Riza; Susilawati (Jurusan Ilmu Pendidikan - Universitas Lampung, 2024)
Early childhood children who are in the 4-5 year range in various developed countries have been introduced to programming concepts, and have even been integrated into the learning curriculum at school. In general, someone's skills in creating programs cannot be immediately acquired or mastered in a short time. In Indonesia, awareness of the importance of developing thinking patterns through computational thinking is still low, especially in areas far from urban areas. Therefore, community service activities are carried out at SDN Cadaskertajaya II, Karawang Regency. The platform used in this activity is MIT App Inventor which is a web-based platform for creating visual block-based device applications. The method used in this activity consists of 2 main stages, namely preparation and implementation. During the training activities, students were very enthusiastic about the material presented. Then, based on the results of the post-test and discussion at the end of the activity, overall this training activity was effective, easy to understand, memorable, useful, as well as interesting and enjoyable.